2006
DOI: 10.1002/ajmg.a.31145
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic analysis of a familial interstitial deletion Xp22.2‐22.3 with a highly variable phenotype in female carriers

Abstract: We describe a familial interstitial deletion of 7.7-Mb involving Xp22.2-22.3. The deletion was transmitted from an asymptomatic mother to her two children with severe developmental delay, no speech development and autistic behavior. Assessment of the deletion boundaries by FISH and PCR analyses indicated that the deletions encompasses 27 genes. Several of these genes are associated with known disorders, like KAL1 (Kallmann syndrome), steroid sulfatase (STS) (X-linked ichtyosis), and arylsulfatase E (ARSE) (cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 16 publications
0
45
0
1
Order By: Relevance
“…These alterations functionally translate into impaired visual processing and retinal output, and suggest that deletion or mutation in NLs may induce important alterations already at sensory synapses and not only in higher brain areas. Of note, mutations in NLs are linked to cases of autism and mental retardation (Jamain et al, 2003;Laumonnier et al, 2004;Chocholska et al, 2006;Lawson-Yuen et al, 2008;Yan et al, 2008), and NL deletion-mutant mice have been introduced as genetic models of autism (Tabuchi et al, 2007;Jamain et al, 2008). In particular, visual alterations have been described in some cases of autism (Cook, 1990;Bertone et al, 2005;Dakin and Frith, 2005), and it will be interesting to explore the impact of other NL isoforms on the organization and function of the retinal network.…”
Section: Functional Consequences Of Nl2 Deficiencymentioning
confidence: 99%
“…These alterations functionally translate into impaired visual processing and retinal output, and suggest that deletion or mutation in NLs may induce important alterations already at sensory synapses and not only in higher brain areas. Of note, mutations in NLs are linked to cases of autism and mental retardation (Jamain et al, 2003;Laumonnier et al, 2004;Chocholska et al, 2006;Lawson-Yuen et al, 2008;Yan et al, 2008), and NL deletion-mutant mice have been introduced as genetic models of autism (Tabuchi et al, 2007;Jamain et al, 2008). In particular, visual alterations have been described in some cases of autism (Cook, 1990;Bertone et al, 2005;Dakin and Frith, 2005), and it will be interesting to explore the impact of other NL isoforms on the organization and function of the retinal network.…”
Section: Functional Consequences Of Nl2 Deficiencymentioning
confidence: 99%
“…Since the first study showing a linkage in a twin sets between the incidence of the ASD and mutations in the NLGN3 and 4 genes, several structural variants (including point mutations, truncations, and exon deletions) of the coding regions of neurexin (NX) and neuroligin (NL) were found to be associated with ASD and mental retardation (1)(2)(3)(4)(5)(6)(7). Emerging evidence also indicates that rare variations in copy number and common variations within the genes encoding NX-1 and NX-3 contribute to ASD susceptibility (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, an R451C mutation within the esterase domain of neuroligin 3 was identified in a Swedish family with two affected boys [25] . Various other mu- tations in NLGN3 and NLGN4X genes have been identified in ASD patients [26][27][28][29][30][31][32] . Some of these mutations were studied at the functional level to reveal their possible linkage with ASD.…”
Section: Neurexins and Neuroliginsmentioning
confidence: 99%